The role of rodents in tropical forest regeneration : seed predation and seed dispersal - Dittel, Jacob W. (My University, 2014)
Small rodents have long been considered to be seed predators rather than effective seed dispersers. Particularly in the Neotropics, this predatory role has been thought to be especially true for large-seeded plant species that likely had mutualistic relationships with megafauna that went extinct after the last ice age. Small rodents are not thought to be dispersers because they presumably eat a large proportion of the seeds or cannot move the large seeds sufficiently far to be effective dispersers. In this study, I tracked the removal of seeds from three different heights of three species of large-seeded trees in central Panama, Attalea butyracea, Astrocaryum standleyanum, and Dipteryx oleifera, and followed the removed seeds to deposition sites in central Panama. Removals were most likely perpetrated by two small rodents, the strictly terrestrial Proechimys semispinosus (Central American spiny rat) and the arboreal Sciurus granatensis (red- tailed squirrel) because they were the most abundant small rodents in the study sites. At each deposition site, I measured 9 microhabitat variables to determine if these two rodents were preferentially depositing seeds at sites with certain characteristics or were randomly depositing seeds. During my study, rodents handled 98 seeds; 12 seeds were taken into subterranean burrows or into the canopy and therefore unlikely to successfully recruit, while only one seed was preyed upon. On average, A. butyracea was moved 6.5 m before being deposited. Astrocaryum standleyanum had an average distance moved of 1.4 m. In all cases, seeds were most likely to be deposited with the fruit eaten, but the seed remained intact. Additionally, rodents deposited seeds in locations with large logs (> 10cm diameter), high herbaceous cover, and an intact canopy. The number of large logs was significantly different from random locations. Despite not being able to determine long-term fate (greater than ca. 1 year), I show that these small rodents are not primarily seed predators and may in fact be important mutualists by dispersing seeds relatively long distances to favorable germination sites.
Keywords: Forest regeneration - Tropics; Seeds - dispersal; Seed dispersal by animals; Granivores